Lead “Contamination / Ligature” Threshold Evaluation in Copper-Based Alloys of the Golden Horde Monuments from the Lower Volga Region - Kseniya S. Kovaleva (Нижневолжский археологический вестник)
The article presents a study of the Golden Horde copper-based alloys to evaluate the threshold that would allow separating contaminated copper and purposefully alloyed with lead. Being a component of some types of ores, lead passed into insufficiently purified dry copper. The lead content can be overestimated in the surface corroded layer and incorrectly recorded during the analytical study of the metal composition. Thus, the contamination threshold, set for other metals at 1%, should additionally be specified for lead. Lead physical properties determine its effect on alloys of which it is a component. Its additive improves copper casting alloys properties, but in general, lead is a harmful impurity, since it contributes to the appearance of brittleness during hot forging. According to written sources, copper unrefined from lead and alloys with lead had limited application and were used for casting medium- and large-sized utensils. A study of 647 copper and copper-based alloy utensil showed that unrefined contaminated copper and its alloys with tin and zinc with a 2–3% average lead content were used for forging in addition to refined copper during the Golden Horde period in the Lower Volga region. Tin bronze and triple, multicomponent bronzes with a 3.5% average lead content were the main casting alloys. Alloys with medium and high lead content (Pb > 10) were used to a limited extent mainly for casting mass-produced objects such as belt fittings, mirrors, connecting rings, etc. It is assumed that in these cases, lead based improver had both technological benefits aimed at improving casting properties, and economic ones, reducing metal production costs. The threshold higher than 2.5–3% of the lead can be considered artificially additions in the Golden Horde alloys of the Lower Volga since these concentrations are stably recorded in forged metal that was not artificially alloyed.